1998
DOI: 10.1007/s002990050384
|View full text |Cite
|
Sign up to set email alerts
|

Agar as a gelling agent: chemical and physical analysis

Abstract: Agars with different performance in bioassays were analysed for physical and chemical properties. Agars with the highest gel strength had the best performance. Good performance was also related to a low pH of a suspension of agars and to a low sulphur content. The diffusion rate of ions in gels differed between agars, but could not explain differences in agar performance. The time of autoclaving had a marked effect on the gel strength, however, without affecting the performance. Chemical analysis revealed larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 7 publications
1
58
0
3
Order By: Relevance
“…A change of medium-pH may have various effects that may influence performance and development of the explants (George et al 2008). (1) In semi-solid media, the availability of many compounds is pH-dependent (Arnon et al 1942;Scholten and Pierik 1998;Van Winkle et al 2003). (2) Uptake of medium components by the explants may be influenced directly by the pH.…”
Section: Introductionmentioning
confidence: 99%
“…A change of medium-pH may have various effects that may influence performance and development of the explants (George et al 2008). (1) In semi-solid media, the availability of many compounds is pH-dependent (Arnon et al 1942;Scholten and Pierik 1998;Van Winkle et al 2003). (2) Uptake of medium components by the explants may be influenced directly by the pH.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in many cases, symptoms of deficiency are only observed in mutants impaired in the uptake of the nutrient in question (Tomatsu et al, 2007;Mills et al, 2008;Assunção et al, 2010). In general, gelling agents may contribute considerable amounts of nutrients (Debergh, 1983;Scholten and Pierik, 1998), hampering the occurrence of deficiency for specific nutrients (Jain et al, 2009). Thus, it becomes crucial to select the most suitable gelling agent when particular nutrient deficiencies are to be obtained.…”
mentioning
confidence: 99%
“…Results further revealed the positive bearings of a low agar concentration in combination with GELRITE on secondary bulblet regeneration, bulblet size, change in diameter, and number of roots per bulblet and root length. It is suggested that low agar concentration increased the availability and uptake of certain nutrients like iron, calcium, and zinc (Mohamed-Yasseen, 2001;Witte et al, 2002) and lowered the concentration of toxic compounds that adversely affect plant growth (Scholten and Pierik, 1998). On the other hand, provision of GELRITE also exerted positive effects on regeneration behavior (Huang et al, 1995).…”
Section: Discussionmentioning
confidence: 99%